P088 Transcriptome landscape of protein-coding genes and long noncoding RNAs in the colon and blood of DSS-induced mouse model of Acute ulcerative colitis. (25th January 2019) - Yarani, R; Palasca, O; Tsankova Doncheva, N; Anthon, C; Pilecki, B; Litman, T; Holmskov, U; Jensen, L J; Gorodkin, J; Pociot, F
Abstract: Background: Ulcerative colitis (UC) is an inflammatory disorder initiating from the rectum and affecting the mucosal lining. Gene expression analysis is a powerful tool for understanding disease development and the underlying pathophysiology. Thus, we used one of the most well established mouse models of UC to investigate the expression changes of protein-coding genes and long noncoding RNAs (lncRNA) in colon and blood of diseased and healthy mice. We further aimed to investigate the most significant biological processes and pathways that these differentially expressed genes are part of. Methods: A dextran sodium sulphate (DSS)-induced mouse model of UC was established by administering DSS to the drinking water at a final concentration of 1.5% (wt/vol) for 7 days. Total RNA (excluding small RNA) from colon tissue and blood samples of 3 DSS-treated and 3 healthy mice was extracted and sequenced by Illumina Hiseq 4000. We obtained an estimate of gene expression level by mapping and quantification to the annotated mouse genome, and then performed differential gene expression and pathway analyses between DSS-treated and control mice. Groups of tightly connected genes were identified by Markov clustering of the STRING functional associations between these genes. Results: Our preliminary analysis identified ~2000 protein-coding genes and ~300 lncRNAs in colon as well as ~500 protein-coding genes and ~50 lncRNAs in blood to be significantly (log FC > 1, p adj < 0.1) differentially expressed between the two groups (mainly up-regulated in DSS-treated mice) (see Figure 1). We also found ~200 common genes up-regulated in DSS-treated mice in both colon and blood. Furthermore, network and functional enrichment analysis showed a strong enrichment of genes in immune system related processes and disease pathogenesis (Figure 2). Conclusions: Our data show a significant differential transcriptional signature between the diseased and the healthy animals that can be used to stratify the two groups. Moreover, this study expands our molecular understanding of putative new targets that may be important in the pathophysiology of UC.